Pengaruh Ekspor, Impor dan Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Provinsi Jawa Timur Tahun 2017-2024 - Adi Putra Pratama; Alfin Maulana; Agus Sarwo Edi; Agung Bayu Murti (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to test and analyze the influence of government exports, imports, and expenditures on economic growth in East Java Province in the 2017–2024 period. The analysis unit in this study covers 38 districts/cities in the region. The data used is secondary data obtained from the Central Statistics Agency (BPS) of East Java Province. The research method used is a quantitative approach with statistical analysis techniques using EViews software version 9. Hypothesis testing was carried out through t-test and F-test to determine the partial and simultaneous influence of independent variables on dependent variables. The results show that partially, the export variable has a significant influence on economic growth, while imports and government spending also show significant influences but with different levels of influence. Simultaneously, these three independent variables—exports, imports, and government spending—have a significant effect on economic growth in East Java Province. These findings indicate that international trade activities and government fiscal policies play an important role in driving regional economic growth. Therefore, local governments are expected to formulate the right strategies to improve export performance, manage imports wisely, and optimize government spending to support sustainable economic development.